2014
DOI: 10.1002/jcc.23758
|View full text |Cite
|
Sign up to set email alerts
|

Why it is sometimes difficult to determine the accurate position of a hydrogen atom by the semiexperimental method: Structure of molecules containing the OH or the CH3 group

Abstract: The semiexperimental (SE) technique, whereby equilibrium rotational constants are derived from experimental ground-state rotational constants and corrections based on an ab initio cubic force field, has the reputation to be one of the most accurate methods to determine an equilibrium structure ( reSE). However, in some cases, it cannot determine accurately the position of the hydrogen. To investigate the origins of this difficulty, the SE structures of several molecules containing either the OH or the CH3 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 63 publications
4
28
0
Order By: Relevance
“…Furthermore, the rotational constants of the deuterated species have sometimes large systematic errors because of the large mass increase. 7 For these reasons, it is important to have reliable predicates for these torsional angles.…”
Section: Determination Of Structural Predicatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the rotational constants of the deuterated species have sometimes large systematic errors because of the large mass increase. 7 For these reasons, it is important to have reliable predicates for these torsional angles.…”
Section: Determination Of Structural Predicatesmentioning
confidence: 99%
“…Moreover, it was observed that, in some cases, the rotational constants of deuterated species do not improve the fits. 7 Furthermore, the system of normal equations of the least-squares method may easily become ill-conditioned (i.e. sensitive to small errors of the input data), in particular for atoms close to the center of mass (in other words, their isotopic substitution does not bring new information).…”
Section: Introductionmentioning
confidence: 99%
“…For molecules with an OH group, the situation is more complicated. 17 It was possible to obtain accurate SE structures for nitrous acid (syn and anti conformers), 18,19 formic acid (syn and anti conformers) 20 as well as glycolaldehyde. 17 On the other hand, for proline 21 and glycidol, 17 the SE rotational constants of the OD species were found to be incompatible with the best structure.…”
Section: Introductionmentioning
confidence: 99%
“…17 It was possible to obtain accurate SE structures for nitrous acid (syn and anti conformers), 18,19 formic acid (syn and anti conformers) 20 as well as glycolaldehyde. 17 On the other hand, for proline 21 and glycidol, 17 the SE rotational constants of the OD species were found to be incompatible with the best structure. Finally, although accurate SE structures could be determined for ethanol (anti conformer) 17 and nitric acid, 22 there was obviously a problem: the rotation-vibration interaction constants (a-constants) of the lowest fundamental vibration could not be reproduced accurately by the ab initio force field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation